Ethics and Sustainability: A synergistic apporoach to corporate responsibility - Nurun Nidha Al Akhras N; Almadina; Ayu Andini; Dini Andriani; Wahyuni (JEKAMI Journal of Accounting, 2024)
This paper explores the interconnected relationship between ethics and sustainability within the framework of corporate responsibility (CR). By integrating ethical principles and sustainability goals, corporations can achieve a synergistic effect that enhances both business performance and societal welfare. The study delves into the theoretical foundations of ethical behavior and sustainable practices, highlighting the role of stakeholder theory and the triple bottom line approach. It examines how ethical decision-making influences sustainable business strategies and vice versa. Through case studies of leading companies such as Unilever, Patagonia, and Interface, the paper illustrates practical applications and benefits of this integrated approach. The findings indicate that businesses committed to ethical practices and sustainability not only meet regulatory and societal expectations but also gain competitive advantages, foster innovation, and ensure long-term profitability. The paper concludes by discussing the challenges in implementing these practices and providing recommendations for future research and corporate policy development to enhance the effectiveness of ethics and sustainability in corporate responsibility